Comparison of clinical and radiologic outcomes between biportal endoscopic transforaminal lumbar interbody fusion and posterior lumbar interbody fusion - Ki-Han You; Jin-Tak Hyun; Sang-Min Park; Min-Seok Kang; Samuel K. Cho; Hyun-Jin Park (Scientific Reports, 2024)
Abstract Biportal endoscopic spinal surgery has become increasingly popular, and indications have expanded. Among these, biportal endoscopic transforaminal lumbar interbody fusion (BE-TLIF) has yielded good results. Herein, we compared the clinical and radiological outcomes of 155 patients treated with BE-TLIF and open posterior lumbar interbody fusion (PLIF) for single-level lumbar degenerative diseases. Clinical outcomes included the visual analog scale for the back (VAS-back) and leg (VAS-leg), Oswestry Disability Index, and EuroQol 5-Dimensions. Radiological parameters and fusion rates were evaluated, and postoperative complications were recorded. In this cohort 68 and 87 patients were treated with BE-TLIF and PLIF, respectively. Both groups showed significant improvements in all clinical parameters compared with baseline, but BE-TLIF exhibited a more significant improvement in VAS-back at 1 and 6 months postoperatively. There were no significant differences in the radiological parameters or fusion rates. BE-TLIF had a significantly longer operation time, whereas PLIF exhibited a significantly higher estimated blood loss and surgical drainage, but no significant differences in postoperative complications. Compared to PLIF, BE-TLIF showed similarly good clinical and radiologic outcomes, with better results in terms of early postoperative outcomes. Thus, BE-TLIF is a viable alternative to PLIF with less back pain at 1 and 6 months postoperatively.